The use of glass beads cultivation system to study the global effect of the ppk gene inactivation in Streptomyces lividans - Nezbedová, S; Bezoušková, S; Kofroňová, O; Benada, O; Rehulka, P; Rehulková, H; Goldová, J; Janeček, J; Weiser, J (Folia microbiologica, 2011)
The glass beads cultivation system developed in our laboratory for physiological studies of filamentous microorganisms supports differentiation and allows complete recovery of bacterial colonies and their natural products from cultivation plates. Here, we used this system to study the global effect of ppk gene disruption in Streptomyces lividans. The ppk encoding the enzyme polyphosphate kinase (P) catalyses the reversible polymerisation of gamma phosphate of ATP to polyphosphates. The resulting are phosphate and energy stock polymers. Because P activity impacts the overall energetic state of the cell, it is also connected to secondary metabolite (e.g. antibiotic) biosynthesis. We analysed the global effects of the disruption of this gene including its influence on the production of pigmented antibiotics, on morphological differentiation, on the levels of ATP and on the whole cytoplasmic protein expression pattern of S. lividans. We observed that the S. lividans ppk mutant produced antibiotics earlier and in greater amount than the wild-type (wt) strain. On the other hand, we did not observe any obvious effect on colony morphological development. In agreement with the function of Ppk, we detected much lower levels of ATP in ppk- mutant than in the wt strain. Proteomic analysis revealed that the genes that were influenced by ppk inactivation included enzymes involved in carbon or nitrogen metabolism, phosphate transport and components of the cell translational machinery. We showed that the synthesis of translation elongation factor Tu is during sporulation much higher in ppk- mutant than in wild-type strain.
Keywords: regulace genové exprese u bakterií; bakteriální proteiny; kultivační techniky; umlčování genů; Bacterial Proteins; Gene Expression Regulation, Bacterial; Gene Silencing; Molecular Sequence Data; Culture Techniques; molekulární sekvence - údaje; Phosphotransferases (Phosphate Group Acceptor); antibakteriální látky; fosfotransferasy s fosfátovou skupinou jako akceptorem; Adenosine Triphosphate; Streptomyces lividans; Anti-Bacterial Agents; adenosintrifosfát